Dimensions of maternal behaviour characteristics in domestic and wildxdomestic crossbred sows - Spinka, M; Illmann, G; de Jonge F; Andersson, M; Schuurman, T; Jensen, P (Applied animal behaviour science, 2000)
We examined the maternal behaviour of seven domestic and seven wildxdomestic primiparous sows during 10 days post partum to investigate two questions: (1) Did maternal behaviour change during domestication? (2) Can the interindividual variability of maternal behaviour be subsumed into a few dimensions of maternal temperament? We recorded: (a) willingness to leave the nest for food on Day 2; (b) reaction to a playback of squeezed piglet distress vocalisation on Day 2; (c) spontaneous nursing behaviour and spontaneous lying-down behaviour on Day 5 (from an overnight video recording); (d) reactions to playbacks of various piglet distress vocalisations on Day 6 and (e) reactions to a human in the 'nest' with piglets on Day 9. Moreover, data on baseline cortisol saliva concentration and its increase during a brief transportation period and novel environment challenge at the age of 5 months were available. Crossbred sows did not differ from domestic ones in any aspect of maternal behaviour except for a higher tendency to terminate final massage during nursings and a higher frequency of changing posture from lying to standing and back during the night. Factor analysis (based on correlation matrix of 11 behaviour and cortisol variables calculated for all 14 sows after removing the effect of breed) indicated that 82% of the variability in the data could be explained by three factors: first, 'calmness' on which low night time frequency of major posture changes, carefulness of lying-down behaviour and high propensity to remain in nursing position after milk ejection loaded positively while cortisol concentrations during challenge loaded negatively; second, 'protectiveness' with high loadings of the reaction scores to the playbacks of piglet distress calls and the human presence near the piglets; and third, 'nursing activity' which was strongly positively associated with nursing frequency, and negatively with the proportion of nutritive nursings and baseline cortisol values. The results indicate that most aspects of pig maternal behaviour have not been significantly changed by domestication and that substantial variability in maternal behaviour exists between sows, perhaps in the form of several behaviour characteristics which encompass both behaviour and endocrine profiles of the sows.